A shot in the arm for renal colic: diclofenac feels the best. Issue 4 (April 2017) - Maurer, Douglas M.
Abstract : N/A: Pathan SA, Mitra B, Straney LD, et al. Delivering safe and effective analgesia for management of renal colic in the emergency department: a double‐blind, multigroup, randomised controlled trial. Lancet . 2016; 387(10032):1999–2007.